2015
DOI: 10.5339/difi.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, demographic, housing and health conditions of Qatari women by status of marriage and implications for family polices

Abstract: This study addressed the problems and issues facing the Qatari family in the wake of rapid socioeconomic development. The study explored housing conditions, health conditions and economic conditions of Qatari women as related to the marital status categories such as never married, married, divorced and widowed across seven administrative regions of Qatar, i.e., at the national level. The data for the study were obtained from the Ministry of Development Planning and Statistics, Qatar Census Data, 2010. Macro-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This contract generally includes agreements about the woman's future activities, such as continued schooling, working outside the home, and in some cases, support in the event of divorce is also included (El-Haddad, 2003;Golkowska, 2014). Divorce rates in Qatar have fluctuated between 7-10% in the last 10 years (Ministry of Development Planning and Statistics, 2014;Shehzad, 2015). These fluctuations added uncertainty to the marital equation for women who, in most cases, cannot initiate divorce (Welchman, 2010).…”
Section: The Qatari Contextmentioning
confidence: 99%
“…This contract generally includes agreements about the woman's future activities, such as continued schooling, working outside the home, and in some cases, support in the event of divorce is also included (El-Haddad, 2003;Golkowska, 2014). Divorce rates in Qatar have fluctuated between 7-10% in the last 10 years (Ministry of Development Planning and Statistics, 2014;Shehzad, 2015). These fluctuations added uncertainty to the marital equation for women who, in most cases, cannot initiate divorce (Welchman, 2010).…”
Section: The Qatari Contextmentioning
confidence: 99%
“…Divorce was reported to adversely affect women more than men, especially in low- and middle-income countries (Hailemariam et al, 2019; Lu et al, 2019). Negative connotations associated with divorce in the Arab world, affecting women more than men, were found in a study conducted in Qatar (Shehzad, 2015). This study of 74,724 Qatari women showed that educated women were less likely to marry and were disadvantaged with regard to living and economic conditions.…”
mentioning
confidence: 99%
“…This study of 74,724 Qatari women showed that educated women were less likely to marry and were disadvantaged with regard to living and economic conditions. Importantly, divorced women were more likely to have psychological and physical problems compared to married women (Shehzad, 2015). Even though both men and women can suffer due to divorce, Leopold (2018) found the suffering of men is often transient, while the suffering of women is usually chronic.…”
mentioning
confidence: 99%